2019
DOI: 10.1177/1756286419835077
|View full text |Cite
|
Sign up to set email alerts
|

Real-life outcomes of teriflunomide treatment in patients with relapsing multiple sclerosis: TAURUS-MS observational study

Abstract: Background: Teriflunomide is a once-daily oral immunomodulatory agent approved for the treatment of relapsing–remitting multiple sclerosis (MS). We aimed to obtain data on the effectiveness, tolerability, and subject satisfaction with teriflunomide (Aubagio®) under clinical practice conditions in unselected MS patients. Methods: This work was a non-interventional, prospective, longitudinal, observational study in 307 sites in Germany. Results: A total of 1128 patients were eligible for the efficacy analysis [6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 25 publications
19
42
0
Order By: Relevance
“…teriflunomide as a first-line choice for at least 95% of eligible RRMS and CIS patients with moderate disease activity, except in women planning pregnancy within a year. Demographic characteristics showed that this real-world cohort had mild to moderate disease activity as indicated by pre-existing relapse activity and EDSS scores, and was older on average than patient cohorts in the phase 3, placebo-controlled TEMSO, TOWER and TOPIC clinical trials, an observation that is consistent with age distributions in other real-world studies with teriflunomide [18,20]. Interestingly, the female population in this cohort had a significantly higher median age than the male population.…”
Section: Plos Onesupporting
confidence: 81%
See 1 more Smart Citation
“…teriflunomide as a first-line choice for at least 95% of eligible RRMS and CIS patients with moderate disease activity, except in women planning pregnancy within a year. Demographic characteristics showed that this real-world cohort had mild to moderate disease activity as indicated by pre-existing relapse activity and EDSS scores, and was older on average than patient cohorts in the phase 3, placebo-controlled TEMSO, TOWER and TOPIC clinical trials, an observation that is consistent with age distributions in other real-world studies with teriflunomide [18,20]. Interestingly, the female population in this cohort had a significantly higher median age than the male population.…”
Section: Plos Onesupporting
confidence: 81%
“…To this end, both the European Medicines Agency (EMA) and the US Food & Drug Administration (FDA) endorse the collection of real-world data to answer questions that cannot be addressed in RCTs and/or to provide ongoing benefit-risk analyses of approved DMTs throughout the product lifecycle [15,16]. A growing number of observational studies of teriflunomide are being reported, including studies on patient-reported outcomes [17][18][19][20][21], MRI endpoints [22], compliance and persistence [23], and pregnancy outcomes [24].…”
Section: Introductionmentioning
confidence: 99%
“…Cladribine is a deoxyadenosine analogue which reduces the pro-inflammatory response through depleting lymphocytes 80 . Teriflunomide is another anti-inflammatory medication used in MS, in which the proliferation of rapidly dividing cells, including activated lymphocytes, is inhibited 81 . This inhibition is believed to reduce the extent of the inflammatory response, and thus reduce CNS injury and demyelination in MS patients.…”
Section: Recent Developments In Ms Treatmentmentioning
confidence: 99%
“…The TAURUS-MS I study was one of the first to report experience with teriflunomide under practice conditions in a real-world MS population. 15 Of note, 49.5% of patients were aged 45 years and above, and 24.8% of the observed patients had been treatment-naïve. In this analysis from the TAURUS-MS I study we demonstrate that patients of all age groups and irrespective of pre-treatment status exhibit a decrease of disease activity in terms of relapses under teriflunomide treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Details of the TAURUS-MS I study (‘Therapie mit Aubagio® unter Praxisbedingungen: Wirksamkeit, Lebensqualität und Verträglichkeit bei Patienten mit schubförmiger Multipler Sklerose’) have been reported previously. 15 In short, this was a non-interventional, prospective, longitudinal study performed by 307 office-based and hospital-based neurologists across Germany from 2014 to 2017. The study was approved locally by the Ethic Committee at the Ruhr-University of Bochum, Faculty of Medicine under number 4874-13, as well as registered in the BfArM public study database under number 2075.…”
Section: Methodsmentioning
confidence: 99%